Linezolid Pharmacokinetics and Its Association with Adverse Drug Reactions in Patients with Drug-Resistant Pulmonary Tuberculosis - Chandrasekaran Padmapriyadarsini; Rajesh Solanki; S. M. Jeyakumar; Anuj Bhatnagar; M. Muthuvijaylaksmi; Bharathi Jeyadeepa; Devarajulu Reddy; Prashanth Shah; Rathinam Sridhar; Vikram Vohra; Namrata Kaur Bhui (MDPI AG, 2023)
We evaluated the relationship between the pharmacokinetic parameters of linezolid (LZD) and development of adverse drug reactions (ADRs) in patients with pulmonary drug-resistant tuberculosis. A prospective cohort of adults with pulmonary multidrug-resistant tuberculosis with additional resistance to fluoroquinolone (MDR-TBFQ+) received treatment with bedaquiline, delamanid, clofazimine, and LZD. Blood samples were collected during weeks 8 and 16 at eight time points over 24 h. The pharmacokinetic parameters of LZD were measured using high-performance liquid chromatography and associated with ADRs. Of the 165 MDR-TBFQ+ patients on treatment, 78 patients developed LZD-associated anemia and 69 developed peripheral neuropathy. Twenty-three patients underwent intense pharmacokinetic testing. Plasma median trough concentration was 2.08 µg/mL and 3.41 µg/mL, (normal <2 µg/mL) and AUC0-24 was 184.5 µg/h/mL and 240.5 µg/h/mL at weeks 8 and 16, respectively, showing a linear relationship between duration of intake and plasma levels. Nineteen patients showed LZD-associated ADRs-nine at week 8, twelve at week 16, and two at both weeks 8 and 16. Thirteen of the nineteen had high plasma trough and peak concentrations of LZD. A strong association between LZD-associated ADRs and plasma LZD levels was noted. Trough concentration alone or combinations of trough with peak levels are potential targets for therapeutic drug monitoring.